(untitled) (Journal of Biomedical Investigation, 2024)
Background: Health status could be impacted by disability, and might affect workplace productivity and quality of life. There appears to be a dearth of studies on the association among health status (HS), disability profile (DP) and work-related quality of life (WRQoL) among workers. Aim: This study investigated the association among HS, DP and WRQoL of staff of a university. Methods: Participants in this cross-sectional study were recruited using a stratified sampling technique. The HS, DP and WRQoL were assessed using Short Form Health Survey (SF-12) Questionnaire, Washington Group Questionnaire and Work-Related Quality of Life Scale respectively. Data were summarized using mean, frequency, percentage and standard deviation. Chi-square test was used to evaluate the association among HS, DP and WRQOL. Mann-Whitney U test was used to evaluate the difference in HS, DP and WRQOL between the academic and non-academic staff. Level of significance was set at p < 0.05. Results: Three hundred and seventy (370) workers participated in the study (46.2±10.15 years; male, 56%) with 52.7% reporting a better HS and 87.8% reporting no disability. About 95.4% had a high level of WRQoL. There was a significant association between HS and DP (p=0.001); HS and WRQOL (p=0.002) as well as DP and WRQoL (p=0.001). There was a significant association between academic qualification and HS (p=0.003). There was a significant difference in health status between the academic and non-academic staff (p=0.02). However, there was no significant difference in disability profile between the academic and non-academic staff (p=0.48) as well as WRQOL (p=0.66). Conclusion: This study concluded that most of the staff of the University of Ibadan had good health status, were without disability and had high level of WRQOL. Efforts should be made to sustain these health parameters among staff members.